Review papersPersonal data protection regarding health protection actions - Jakubowicz, Jędrzej; Jakubowicz, Oliwia; Żaba, Czesław; Żaba, Ryszard; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Norms regarding personal data protection are included in the personal data protection bill from 29 September 1997. This article constitutes an outline of the most important legal regulations concerning the issue of personal data protection in the health services.